The Connection of Distribution Location with Primate Kinship in Indonesia Based on Cytochrome B In Silico Analysis - Hernanda, Raden Mochammad Irvan; Ramadhanty, Asmara Nabila; Haryanti, Annisa; Prakasaditya, Yudhistira; Camin, Yeremiah Rubin (Bioinformatics and Biomedical Research Journal, 2019)
Primates are mammals in the animal kingdom and they are terestrial creatures. Primates in Indonesia approximately has 59 species and 79 subspecies which has different sizes and characteristics. Primates are arboreal creatures that spend most of their days hanging on trees for socializing, eating, and exploring. Those factors could be the reason why primates likes to migrate. Evolution by definition is the changes in the genes between the ancestor and its decendants in a long period of time. The cause of evolution varies from the earth geography, adaptability, natural selection, mating, dan mutation. Primates undergo progressive evolution which indicates its abilites to survive in different kinds of environment. This analysis is being used to find out the connection between area distribution and primates genetics in Indonesia based on Cytochrome B in silico analysis. Based on the Cytochrome B MEGA gene analysis and regional mapping using QGIS, the result of it is primates in Indonesia has genetic connection molecularly. Differentiation is not only caused by geographical changes but also by wide imigration activity. Primatesendemicity is not linier to the imigration activity.